2018
DOI: 10.1073/pnas.1807915115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and veterinary trypanocidal benzoxaboroles target CPSF3

Abstract: African trypanosomes cause lethal and neglected tropical diseases, known as sleeping sickness in humans and nagana in animals. Current therapies are limited, but fortunately, promising therapies are in advanced clinical and veterinary development, including acoziborole (AN5568 or SCYX-7158) and AN11736, respectively. These benzoxaboroles will likely be key to the World Health Organization's target of disease control by 2030. Their mode of action was previously unknown. We have developed a high-coverage overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(132 citation statements)
references
References 50 publications
2
129
0
1
Order By: Relevance
“…Recent studies of AN7973 demonstrated that its trypanicidal activity results from inhibition of trypanosome mRNA processing 45 . Furthermore, related HAT and AAT lead compounds, also 6-amides like AN7973, target Cleavage and Polyadenylation Specific Factor 3 (CPSF3), an endonuclease that functions in mRNA processing 46 . It is known that other oxaboroles inhibit CPSF3 in Plasmodium falciparum 28 , and Cryptosporidium CPSF3 is greater than 40% identical to that of P. falciparum at the amino acid level.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of AN7973 demonstrated that its trypanicidal activity results from inhibition of trypanosome mRNA processing 45 . Furthermore, related HAT and AAT lead compounds, also 6-amides like AN7973, target Cleavage and Polyadenylation Specific Factor 3 (CPSF3), an endonuclease that functions in mRNA processing 46 . It is known that other oxaboroles inhibit CPSF3 in Plasmodium falciparum 28 , and Cryptosporidium CPSF3 is greater than 40% identical to that of P. falciparum at the amino acid level.…”
Section: Discussionmentioning
confidence: 99%
“…T. brucei and others in the class kinetoplastida primarily regulate gene expression post-transcriptionally based on transcript stability mediated by 5’ and 3’ UTRs (19). Thus, previous production of overexpression libraries, based on whole-genome fragmentation and cloning (20, 21), cannot ensure that individual ORFs are similarly activated upon induction. To mitigate these problems, we produced a T. brucei ORFeome using PCR amplification, which ensures the placement of each ORF under the same inducible gene regulation system.…”
Section: Resultsmentioning
confidence: 99%
“…Over-expression of the gene yielded a notable loss of activity [96]. Elegant experiments using a gene over-expression library, followed by a selection of clones over-expressing genes yielding reduced sensitivity to acoziborole itself, also identified CPSF3 [97], and over-expression confirmed loss of sensitivity, pointing to CPSF3 as a target, if not the exclusive target, of these compounds in trypanosomes.…”
Section: Acoziborole: Mode Of Action and Resistance Riskmentioning
confidence: 93%